The Geothermal manifestations linkage with the Siulak Fault segment in Kerinci: Structural Geology and Geothermal - Hari Wiki Utama (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2023)
Geothermal manifestation on the Sungai Medang and Semurup, Kerinci Regency appear along the Sumatran Fault System. Geological setting as well as this are interesting things to understand from the linkage between of them. To know this process, it is necessary to understand the fault structure mechanism and the presence geothermal features manifestations. The aim of this research in addition to understanding the linkage between of them, which comprehend the fault mechanism of the fault structure, so as to know the role of the fault structure in the appearance of geothermal features manifestation. Geothermal manifestation in Sungai Medang has geothermal features manifestation surface including hot spring, hot pool, geyser dome, hydrothermal alteration rock, sinter silica, and carbonate sinter. The fault structure measured and analysis on the eastern part of Siulak Fault segment of the Sungai Medang was found to be a normal right slip fault, but western part of Siulak Fault segment on the Semurup which strike-slip fault and normal right slip fault. The existence of geothermal features manifestation surface in fault zone of Siulak Fault segment is evidence that, the role of faults is as a controlled by apeear geothermal manifestation. The fault structure mechanism is the result of dextral movement of Siulak Fault which forms a pull-apart basin. This basin is single fault-bend basin as one master fault of active segment. The fault regime stress analysis obtained direction compressional force is trending north-northwestern and south-southeastern. This regime stress is locally stress on Sungai Penuh Basin.